Arms and the Man: Strategic Trade Control Challenges of 3D Printing - Arjun Banerjee (International Journal of Nuclear Security, 2018)
3D printing is on the verge of confronting Customs and other security agencies with a whole new set of mind-boggling problems. With the tremendous reach of the Internet worldwide, virtual blueprints to weapon parts, components and accessories of drones, narcotic drugs and psychoactive substances, all strategic trade items, as well as other restricted items such as pornographic material, can be proliferated and printed out swiftly by any individual or organization with access to a 3D printer. Intellectual Property Rights are also endangered by these machines. Technology is forever outpacing fast antiquating legal institutions, and security systems, which require revamping to tackle impending threats looming ominously in the horizon. Upgrading the Multilateral Export Control Regimes well in time to incorporate novel trade control challenges posed by 3D printing is the need of the hour. This article proposes to look into the impending threats looming ominously in the horizon in this brave new world of manufacturing evolution and revolution, and the means to counter them.